The high precision measurement of the 144Ce activity in the SOX experiment. Issue 1 (January 2016) - Noto, L Di; ,; Agostini, M; Althenmüller, K; Appel, S; Bellini, G; Benziger, J; Berton, N; Bick, D; Bonfini, G; Bravo—Berguño, D; Caccianiga, B; et al.
Abstract: In order to perform a resolutive measurement to clarify the neutrino anomalies and to observe possible short distance neutrino oscillations, the SOX (Short distance neutrino Oscillations with BoreXino) experiment is under construction. In the first phase, a 100 kCi 144 Ce- 144 Pr antineutrino source will be placed under the Borexino detector at the Laboratori Nazionali del Gran Sasso (LNGS), in center of Italy, and the rate measurement of the antineutrino events, observed by the very low radioactive background Borexino detector, will be compared with the high precision (< 1%) activity measurement performed by two calorimeters. The source will be embedded in a 19 mm thick tungsten alloy shield and both the calorimeters have been conceived for measuring the thermal heat absorbed by a water flow. In this report the design of the calorimeters will be described in detail and very preliminary results will be also shown.